2010
DOI: 10.1063/1.3430008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and mechanism studies of dielectric barrier discharges generated at atmospheric pressure

Abstract: Studies on nanosecond pulsed atmospheric pressure discharge with particle-in-cell Monte Carlo collision simulation Phys. Plasmas 19, 093510 (2012) The discharge condition to enhance electron density of capacitively coupled plasma with multi-holed electrode Phys. Plasmas 19, 093508 (2012) Atomic gas temperature in a nonequilibrium high-intensity discharge lamp determined from the red wing of the resonance mercury line 254nm J. Appl. Phys. 112, 053304 (2012) Diagnostics development for quasi-steady-state operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…2(c), the microdischarge channels continue increasing, with the plasma becoming more homogeneous. This is in agreement with the work that we reported [2]. It is also found that the brightness of the discharge region increases with the deposited power, due to the augmentation of the microdischarge channels.…”
supporting
confidence: 94%
“…2(c), the microdischarge channels continue increasing, with the plasma becoming more homogeneous. This is in agreement with the work that we reported [2]. It is also found that the brightness of the discharge region increases with the deposited power, due to the augmentation of the microdischarge channels.…”
supporting
confidence: 94%
“…These discharges are usually generated in the space between two parallel electrodes, at least one of these being covered with a dielectric layer. This dielectric barrier allows the control of the charge, the energy and the distribution of the micro‐discharges over the entire electrode 17, 18. During the process, the precursor is diluted in a carrier gas (usually helium, argon, or nitrogen) and injected between the two plates to manufacture a plasma film.…”
Section: Introductionmentioning
confidence: 99%
“…However, with a bigger discharge gap, the overvoltage is not sufficient to generate a lot of microdischarges as at a smaller discharge gap, so the filamentary discharge is developed. Li et al [30] and Tang et al [35] had reported that there will be more space charges produced in the discharge channel than in neighborhoods in filamentary discharge. In this case, the space charge distribution is not uniform, which will be significantly improved when the airflow is blown into the discharge gap, so the more uniform discharge can be obtained.…”
Section: B Effect Of Airflow On the Uniformity Of The Nanosecond Pulmentioning
confidence: 99%